Infodemic vs. Pandemic Factors Associated to Public Anxiety in the Early Stage of the COVID-19 Outbreak: A Cross-Sectional Study in China - Xu, Jian; Liu, Cong (Frontiers in Public Health, 2021)
Introduction: Every outbreak of an epidemic or pandemic disease is accompanied by the tsunami of information, which is also known as the infodemic. Infodemic makes it hard for people to find trustworthy sources and reliable guidance when they need it, and causes social panic about health, widens the gaps between races and regions, and even brings the social chaos all over the world. While most researchers and related parties made efforts to control the inaccurate information spreading online during the COVID-19 pandemic, the infodemic influence caused by the overload of accurate information were almost or completely ignored, and this will hinder the control of infodemic in future public health crises. This study aims to explore the infodemic vs. pandemic influence on people's psychological anxiety across different media sources in the early stage of the COVID-19 outbreak in China. Methods: A cross-sectional study using online survey method was conducted by a data-collection service provider in April 2020. A total of 1,117 valid samples were finally collected from 5,203 randomly invited members via webpages and WeChat. The sample distribution covered the 30 provincial administrative divisions of mainland China. Results: Hierarchical regression analysis for the potential pandemic sources and infodemic sources of psychological anxiety showed that the infodemic factors of attention to the coronavirus information (β = 0.154, p < 0.001) and commercial media exposure (β = 0.147, p < 0.001) is positively related to the level of anxiety. Statistics indicated that influence of the infodemic factors is over and above that of the pandemic factors (ΔR2 = 0.054, F = 14.199, and p < 0.001). Mediation analysis showed that information overload (B = 0.155, Boot SE = 0.022, and 95% Boot CI [0.112, 0.198]) mediates the link between attention to coronavirus information and anxiety; both information overload (B = 0.035, Boot SE = 0.014, and 95% Boot CI [0.009, 0.062]) and media vicarious traumatization (B = 0.106, Boot SE = 0.017, and 95% Boot CI [0.072, 0.140]) mediate the link between commercial media exposure and anxiety. Conclusion: This study suggested that the influence of infodemic with mixed accurate and inaccurate information on public anxiety does exist, which could possibly go beyond that of the pandemic. Information overload and vicarious traumatization explain how infodemic may be associated to public anxiety. Finally, commercial media could be a major source of infodemic in the Chinese media context. Implications for the related parties were discussed.